2011
DOI: 10.1007/s10195-011-0134-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-reducible knee dislocation with interposition of the vastus medialis muscle

Abstract: Irreducibility of the knee following complete dislocation is a rare event determined by the interposition of various capsulo-ligamentous structures in the joint space. Such cases often require urgent surgical treatment. We report the case of a healthy 70-year-old man with a sprain of the left knee that occurred after a sports trauma. The patient showed knee dislocation with multiple ligamentous injuries and articular block due to interposition of a portion of the vastus medialis muscle. After arthroscopic eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…There is still no consensus as to the best surgical method, and treatment options range from arthroscopic debridement of the capsule-ligament structures (28) to open reduction and removal of the muscle interposition (14,(29)(30)(31). In cases of muscle dislocation different surgical choices are advocated: sectioning of the muscle to allow reduction of the knee dislocation (27) or repair of the muscle rupture to return the muscle to its anatomical site (29). Durakbaşa et al reported that the medial meniscus may often be detached from the meniscocapsular junction and in these cases it is necessary to extract the medial meniscus from the joint to reduce the dislocation (32).…”
Section: J Ointsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still no consensus as to the best surgical method, and treatment options range from arthroscopic debridement of the capsule-ligament structures (28) to open reduction and removal of the muscle interposition (14,(29)(30)(31). In cases of muscle dislocation different surgical choices are advocated: sectioning of the muscle to allow reduction of the knee dislocation (27) or repair of the muscle rupture to return the muscle to its anatomical site (29). Durakbaşa et al reported that the medial meniscus may often be detached from the meniscocapsular junction and in these cases it is necessary to extract the medial meniscus from the joint to reduce the dislocation (32).…”
Section: J Ointsmentioning
confidence: 99%
“…In the literature, there is no universal agreement as to whether and when lesions of the cruciate ligaments should be repaired. A one-step reduction method combining arthroscopic cruciate ligament reconstruction is described (29,33). In this kind of lesion, Bistolfi et al (29) confirmed that lateral and rotational stability must be achieved immediately by reconstruction or suture of the peripheral structures, while reconstruction of the cruciate ligaments can be postponed and even avoided in elderly patients or those not professionally engaged in high level sports.…”
Section: J Ointsmentioning
confidence: 99%
“…[1][2][3] This injury typically occurs when a valgus force is applied to a flexed knee with external rotation of the tibia. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The medial femoral condyle button-holes through the torn medial capsuloligament complex as a flexed knee is forced into severe valgus. As the deforming force dissipates, the knee partially reduces.…”
mentioning
confidence: 99%
“…Over the past two decades, open reduction has been the most widely used method for the management of irreducible posterolateral knee dislocation. [4][5][6][7][8][9][10][11][12][13][14] Although this method is simple and reportedly yields satisfactory clinical outcomes, it can cause further damage to the torn medial structures and could result in fluid extravasation into the soft tissues around the joint during cruciate ligament reconstruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation